KEY INFORMANTS’ PERSPECTIVES ON FOOD SECURITY AMONG FEMALE-HEADED HOUSEHOLDS IN KENYA - Icheria, Beatrice Kabui; Carbonatto, Charlene Laurence; Bila, Dr Nontembeko Joyce (Social Work/Maatskaplike Werk, 2021)
Social connectedness plays an important role in protecting food security, which requires multidisciplinary input from fields such as nutrition, agriculture, public health, social work and community development. This qualitative study explored food security among female-headed households (FHHs) in Kenya, as part of a larger mixed methods doctoral study. Fifteen key informants monitoring food security were interviewed in the qualitative phase and the thematic analysis generated nine themes, of which two are discussed. Results reveal that dietary diversity in FHHs is poor: they often experience severe food insecurity. Recommendations for practice, policy, and future research are provided.